Comprehensive COMPARE database reduces allergenic risk of novel food proteins. Issue 1 (31st December 2022) - Herman, Rod A.; Song, Ping
ABSTRACT: The comprehensiveness of the allergen database used to bioinformatically compare a novel food protein with known allergens is critical to the ability to assess the allergenic risk of newly expressed proteins in genetically engineered crops. The strength of the relationship between a candidate GE protein's amino acid sequence and that of known allergens is used to predict cross-reactive risk. The number of truly novel allergen sequences added annually to the COMPARE database reflects on the comprehensiveness of our knowledge of allergen amino acid sequence diversity. Here, we investigated the most recent five years of updates to the COMPARE allergen database for truly novel entries. Results indicate that few truly novel sequences are added each year, suggesting that the database and our knowledge of allergen sequence diversity is currently quite comprehensive, and that current in silico prediction of allergenic risk for novel food proteins is robust.